Superparamagnetic Core-Shell-Type Fe3O4/Ru Nanoparticles as Catalysts for the Selective Hydrogenation of an Unconstrained α,β-Unsaturated Ketone - Khan, Farooq-Ahmad; Süss-Fink, Georg (My University, 2012)
Superparamagnetic core-shell-type Fe3O4/Ru nanoparticles (particle size ca. 15 nm) synthesized by co-precipitation, adsorption and reduction methods were found to selectively hydrogenate the carbon-oxygen double bond in trans-4-phenyl-3-penten-2-one (conversion 100 %, selectivity > 90 %) with a catalytic turnover of 900 under mild reaction conditions (30 °C, 15 bar H2). The finely dispersed catalyst can be separated from the reaction mixture by using an external magnet, recycled, and reused without significant loss of activity and selectivity.
Keywords: Nanoparticles; Ruthenium; Hydrogenation; Supported catalysts